1993
DOI: 10.1213/00000539-199303000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Laudanosine Levels in Patients Given Atracurium During Liver Transplantation

Abstract: Atracurium, a nondepolarizing muscle relaxant, does not depend on the liver for clearance, but its principal metabolite, laudanosine, is eliminated primarily by the liver and is potentially neurotoxic. We measured atracurium and laudanosine levels in 15 adult patients during the three stages of liver transplantation to assess the effect of major impairment of liver function. Atracurium was given in a bolus dose of 0.5 mg/kg followed by continuous infusion at a rate adjusted to maintain 95-99% of total neuromus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…infusion was commenced in the other arm for 51W89 administration. A bolus dose of 51W89 0.1 mg kg 91 (2 ED95 [10,11]) was then given into the infusion over 10 s. Additional blood samples were obtained at 2,4,6,8,10,12,15,20,25,30,45,60, 90, 120, 240 and 480 min. After preliminary results were available from the first 12 patients, an additional sample was obtained at 150 min (this included the last eight healthy patients and the last 13 renal failure patients).…”
Section: Methodsmentioning
confidence: 99%
“…infusion was commenced in the other arm for 51W89 administration. A bolus dose of 51W89 0.1 mg kg 91 (2 ED95 [10,11]) was then given into the infusion over 10 s. Additional blood samples were obtained at 2,4,6,8,10,12,15,20,25,30,45,60, 90, 120, 240 and 480 min. After preliminary results were available from the first 12 patients, an additional sample was obtained at 150 min (this included the last eight healthy patients and the last 13 renal failure patients).…”
Section: Methodsmentioning
confidence: 99%
“…With such doses, respiratory assistance is necessary. Clinical studies (15,16) have reported that the plasma concentration of iaudanosine was usually less than 0.5 mg/L. Moreover, if cisatracufium is used, the plasma concentrations of laudanosine are even lower.…”
Section: Case Historymentioning
confidence: 99%
“…A laudanosina atravessa a barreira hematoencefálica e pode ser encontrada no líquido céfalo-raquidiano com elevado potencial de neurotoxicidade (Lawhead et al, 1993).…”
Section: Atributos Principais Para Atender a Finalidade Da Pesquisaunclassified
“…As concentrações plasmáticas do atracúrio permanecem constantes durante as fases pré-anepática e anepática, mas diminuem no final da fase neo-hepáitca, visto que as concentrações da laudanosina aumentam em cada fase (Lawhead et al, 1993). Consequentemente, o acumulo da laudanosina foi observado nos pacientes com hepatite fulminante que aguardavam o TOF e receberam infusão contínua de atracúrio para facilitar a ventilação mecânica dos pulmões.…”
Section: Atributos Principais Para Atender a Finalidade Da Pesquisaunclassified